2010
DOI: 10.1007/s00003-010-0630-y
|View full text |Cite
|
Sign up to set email alerts
|

Odor and taste perception at normal and low atmospheric pressure in a simulated aircraft cabin

Abstract: During flights, reduced odor and taste perception is reported. Passengers tend to prefer spicier meals than on the ground. The conditions on board were simulated at the Fraunhofer flight test facility in Holzkirchen, Germany, consisting of a front fuselage of an Airbus A310-200 in a huge metal tube in which all relevant parameters can be adjusted (humidity, temperature, pressure). Flight tests were carried out at low atmospheric pressure corresponding to cabin conditions on board at cruising altitude and were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 21 publications
2
16
0
Order By: Relevance
“…Also in line with earlier findings [ 2 ], we observed no effect of pressure on odor discrimination, but the gustatory score was significantly reduced. As with previous results [ 1 ], the higher taste thresholds for salty drove the gustatory score reduction. The lower (better) threshold for sweet, however, is discordant with earlier findings [ 1 ], whereas the threshold constancy of sour and bitter tastants is in line with those results.…”
Section: Resultssupporting
confidence: 90%
See 3 more Smart Citations
“…Also in line with earlier findings [ 2 ], we observed no effect of pressure on odor discrimination, but the gustatory score was significantly reduced. As with previous results [ 1 ], the higher taste thresholds for salty drove the gustatory score reduction. The lower (better) threshold for sweet, however, is discordant with earlier findings [ 1 ], whereas the threshold constancy of sour and bitter tastants is in line with those results.…”
Section: Resultssupporting
confidence: 90%
“…We tested the threshold using only one odor (n-butanol), which obviously is not representative of daily life smell perception. As Burdack-Freitag et al reported [ 1 ], sensitivity for many other odors will decrease in a hypobaric atmosphere, and safety-related alert systems in hypobaric environments should be based on automatic sensors.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…And airplane travel in particular may affect other sensory functions as well. During simulated flights, healthy volunteers experienced changes in their gustatory detection thresholds [5]. As a consequence, commercial airlines have refined their in-flight meals to compensate for these flight-related sensory alterations.…”
Section: Introductionmentioning
confidence: 99%